War, Housing Rents, and Free Market: Berlin's Rental Housing during World War I - Konstantin A. Kholodilin (European Review of Economic History, 2016)
New archival evidence on housing rents in Berlin over 1909–1917 is presented. The data are extracted from newspaper announcements and georeferenced. Using hedonic regressions, quality-adjusted rent indices are constructed and employed to analyze the rental dynamics during World War I, when housing market experienced several shocks. The outbreak of the war led to an outflow of men from cities. Toward the end of the war, the construction freeze together with an inflow of workers and discharged soldiers resulted in a housing shortage. The analysis shows a rent decline (particularly for cheap dwellings) during the first half of the war, followed by a moderate increase. In 1917, given a dramatic overall price increase, real rents lost half of their value. Thus, regulatory policy did not emerge as a result of market failure, but rather the fear of rapid rent increases as a consequence of the supply stagnation despite growing housing demand.
Additional information: This is a pre-copyedited, author-produced version of an article accepted for publication in European Review of Economic History following peer review. The version of record War, Housing Rents, and Free Market : A Case of Berlin's Rental Housing Market during World War I. Konstantin A. Kholodilin. In: European Review of Economic History. - 20 (2016), 3, S. 322-344 is available online at: http://dx.doi.org/10.1093/ereh/hew008
Keywords: 330